Pendampingan UMKM Melalui Pemberdayaan Petani Cokelat Dalam Peningkatan Produksi dan Supply Chain - Reniati, Reniati; Zukhri, Nizwan; Hamsani, Hamsani; Pronika, Yeni; Setiawan, Adi (Yumary: Jurnal Pengabdian kepada Masyarakat, 2025)
Purpose: This program aims to strengthen the cocoa bean supply chain by empowering local farmers through training in cultivation, post-harvest management, and business partnership, supporting MSME’s Cokelat Candu in Pangkal pinang, Bangka Belitung. Methodology/approach: This program was implemented in Pangkalpinang, Bangka Belitung (May–October 2025) with 40 participants and through coordination with the Department of Agriculture and Cooperatives of MSMEs, surveys, focus group discussions (FGDs), training, mentoring, field observations, and interviews with farmers and MSMEs. Results/findings: The program successfully improved farmers’ knowledge and skills in cocoa cultivation and post-harvest management, resulting in higher bean quality and a more stable raw material supply for the Cokelat Candu MSME’s. Key outputs included enhanced farmer capacity, stronger collaboration through the Bangka Kovertur Community (KOKOA), new innovative products such as premium chocolate bars and instant cocoa powder. The activity also fostered synergy between academia, local government, and business actors in creating a sustainable supply chain. Conclusion: Empowering local cocoa farmers has proven effective in improving production quality and ensuring the sustainability of the cocoa supply chain. Strengthening cooperation between farmers and Chocolate MSME’s not only contributes to increasing business competitiveness but also encourages sustainable local economic growth in Bangka Belitung. Limitations: The number of farmers and MSME’s still limited in one region, its evaluation was conducted in the short term. Contribution: This study contributes to agricultural economics, rural development, and entrepreneurship by strengthening local economic resilience through farmer and MSME’s linkages and offering a replicable model for empowering farmers and improving MSME’s competitiveness.